P0948 Subclinical Coronary Microvascular Dysfunction in Inflammatory Bowel Disease: Echocardiographic Assessment Using the Cold Pressor Test - S Mustapic; M Kumric; I Akrapovic Olic; P M Živković; T Svagusa; D Dohoczky; M Banic; J Bozic (Journal of Crohn’s and Colitis, 2026)
Abstract Background Chronic inflammation in IBD contributes to endothelial dysfunction and an increased cardiovascular risk. Coronary microvascular dysfunction (CMD), a precursor of atherosclerosis, can be noninvasively assessed by coronary flow velocity reserve (CFVR) using transthoracic Doppler echocardiography (TTE). The cold pressor test (CPT) is a sympathetic stimulus that elicits endothelium-dependent coronary vasodilation and functional evaluation of coronary microcirculation. Data on impaired CFVR in IBD remains limited. This study aimed to assess coronary microvascular function (CMF) in IBD patients compared to healthy controls (HC) using echocardiography-derived CFVR during CPT induced hyperemia. Methods This cross-sectional study included 13 IBD patients and 15 age and sex matched HC, recruited at the University of Split School of Medicine. All participants underwent TTE with visualization of the mid left anterior descending artery (Figure 1). CPT was performed by immersing the right hand into ice-water for 3 minutes. CFVR was calculated as the ratio of hyperemic to baseline maximal diastolic flow velocity. Brachial blood pressure (BP) and heart rate (HR) were measured at baseline, during, and after the CPT to confirm systemic hemodynamic response. All measurements were performed under standardized conditions by the same operator, blinded to group allocation. Results CFVR was significantly lower in patients with IBD compared with HC (2.5 (2.2-3.1) vs. 3.0 (2.8-3.2), P = 0.024) (Figure 2). A CFVR value below 2.0, indicative of impaired CMF, was observed in 4 of 13 patients with IBD, and in none of the HC. During the CPT, all participants demonstrated an increase in HR and diastolic BP, confirming an adequate sympathetic response. However, systolic BP failed to rise in 5 of 13 participants in the IBD group and in 5 of 15 HC. A sensitivity analysis excluding these individuals demonstrated that the lower CFVR observed in the IBD group was not attributable to suboptimal hyperemic stimulation, as the between-group difference remained statistically significant. Conclusion Patients with IBD exhibited significantly lower CFVR compared with HC, indicating the presence of subclinical CMD likely related to chronic systemic inflammation. The CPT effectively elicited sympathetic activation in both groups, supporting its feasibility as a noninvasive physiological stressor in IBD patients. These findings suggest that even in the absence of overt cardiovascular disease, IBD may be associated with early impairment of CMF. The main limitations of this study are its small sample size and the use of a single noninvasive modality, which may limit generalizability and mechanistic inference. References: Microvasc Res. 2015;97:25-30. doi:10.1016/j.mvr.2014.08.003 Expert Rev Cardiovasc Ther. 2019;17(4):305-318. doi:10.1080/14779072.2019.1598262 Eur Cardiol. 2015;10(1):12-18. doi:10.15420/ecr.2015.10.01.12 Conflict of interest: Mustapic, Sanda: No conflict of interest Kumric, Marko: No conflict of interest Akrapovic Olic, Ivna: No conflict of interest Živković, Piero Marin: No conflict of interest Svagusa, Tomo: No conflict of interest Dohoczky, David: No conflict of interest Banic, Marko: No conflict of interest Bozic, Josko: No conflict of interest